SPATIAL ANALYSIS OF LANDSLIDE HAZARD POTENTIAL FOR DISASTER MITIGATION-BASED SPATIAL PLANNING IN THE CITY OF SABANG - Razali Amna; Syamsidik; Muksin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
The geology and topography of Sabang City has the characteristics of areas that have the potential for landslides. This study analyzes the potential for landslide hazard to spatial planning as a disaster mitigation effort. Identification of potential landslide hazards using a geographic information system (GIS), based on the assessment and weighting of the factors that cause and trigger landslides. The results of the analysis of the level of landslide hazard potential are prepared by a landslide hazard map based on the influence of each parameter that causes landslides. The results of the analysis show that the area with a high landslide hazard potential of 8.98% or 1,114.60 Ha in Suka Jaya District. The area of ​​moderate landslide hazard potential is 85.73% or 10,639.88 Ha covering Suka Jaya and Suka Karya Districts. The results of a comparison of high landslide hazard potential with spatial patterns show that high landslide hazard potential is found in spatial patterns of dense settlements of 23%. Mixed plantation area 13%, protected forest 12%, tourist area 12%, residential area 11%, industrial area 7%. The results of the research are expected to be taken into consideration in the spatial planning of Sabang City, to apply the Regulation of the Minister of Public Works Number 22/PRT/M/2007 concerning Guidelines for Spatial Planning for Landslide Disaster Areas in Areas with High potential for landslide hazard. industrial area 7%. The results of the research are expected to be taken into consideration in the spatial planning of Sabang City, to apply the Regulation of the Minister of Public Works Number 22/PRT/M/2007 concerning Guidelines for Spatial Planning for Landslide Disaster Areas in Areas with High potential for landslide hazard. industrial area 7%. The results of the research are expected to be taken into consideration in the spatial planning of Sabang City, to apply the Regulation of the Minister of Public Works Number 22/PRT/M/2007 concerning Guidelines for Spatial Planning for Landslide Disaster Areas in Areas with High potential for landslide hazard.